China's relations with Arabia and the Gulf, 1949-1999 - Bin Huwaidin, Mohamed, 1969- (Durham modern Middle East and Islamic world series, 2002)
This book provides a detailed analysis of China's foreign policy towards the Gulf and Arabian peninsula region from the establishment of the People's Republic of China in 1949 to the end of the 20th century. Based on extensive original research, it looks at the relations between China and each of the countries of the region over the entire period. It demonstrates that two key factors have shaped China's foreign policy with the region - China's relations with the United States and the Soviet Union, and China's drive to increase its economic ties with the countries of the region, especially afte.